Studi Kasus Asuhan Keperawatan Pada Ibu P4A2 Dengan Post Sectio Caesarea A/I Fetal Compromised Krisis Hipertensi - Endah Dwi Kusuma; Dwi Sri Handayani (JOURNAL SAINS STUDENT RESEARCH, 2026)
Sectio caesarea is a surgical procedure to deliver the fetus through an incision in the abdomen and uterus, performed for specific indications to save the mother or the fetus. The post-sectio caesarea condition requires comprehensive nursing care because it can lead to various physical and psychological problems during the recovery period. This case study aims to describe the implementation of nursing care in a patient with a medical diagnosis of post-sectio caesarea due to fetal compromise and hypertensive crisis in the delivery room. The method used is a descriptive case study with a nursing process approach including assessment, nursing diagnosis, intervention, implementation, and evaluation. The subject of this case study was Mrs. S P4A2 with a medical diagnosis of post-sectio caesarea due to fetal compromise and hypertensive crisis. The assessment results showed that the patient experienced surgical wound pain, breast milk had not yet been produced, and she felt weak and afraid to move. The nursing diagnoses identified were acute pain, ineffective breastfeeding, and activity intolerance. After two days of nursing care, the patient's condition showed good progress, characterized by decreased pain, improved breastfeeding ability, and gradually increased activity tolerance. Comprehensive nursing care plays an important role in supporting the recovery process of post-sectio caesarea patients.